ANALISIS KINERJA KEUANGAN PT. BANK 9 JAMBI PERIODE 2017-2019 - Silvia Rahayu (Institut Agama Islam Negeri Kerinci, 2022)
ABSTRACT The purpose of this research is to find out how the performance of PT. Bank 9 Jambi based on Financial Ratio Analysis for the period 2017-2019. The data used is secondary data published through the official website of bank jambi, namely BankJambi.co.id. then analyzed using the ratio of Liquidity, Solvency and Profitability. The data used used is annual data from 2017-2019. The results of the Quick Ratio in 2017-2019 is said to be Not Good. Based on the results of the Banking Ratio in 2017-2019 it is said to be less good. Based on the results of the Asset To Loans Ratio in 2017-2019 it is said to be very good. While the solvency Ratio based on the results of the Primary Ratio in 2017-2019 is said to be Good. Based on the Capital Ratio in 2017-2019 it is said to be not Good. Based on the results of the Capital Adequacy Ratio in 2017-2019 it is said to be very Good. While the Profitability Ratio based on the result of the Gross Profit Margin is said to be very Good . based on the results of Return On Asset said to be very Good. Based on the result of Return On Equity said to be very Good.